An AN OVERVIEW OF THE LEVEL OF SOCIETY KNOWLEDGE ABOUT CT SCAN IN CONDONGCATUR VILLAGE - Siti Arifah (NHM PRESS, 2022)
CT Scan examination is a radiological diagnostic tool that uses a computer to reconstruct data from the absorption capacity of a particular tissue or organ that has been penetrated by a thin beam of x-rays and captured by a detector. The lack of public knowledge about CT Scan examinations can cause this examination to be considered dangerous so that movements often occur when carrying out the examination so that a repeat examination must occur. This type of research is descriptive quantitative. This research was conducted in the village of Condongcatur, Depok, Sleman, Yogyakarta in July 2022. The results of the study were obtained from 100 respondents from the Condongcatur village community regarding CT Scan examinations. Based on the frequency distribution of the characteristics of the knowledge level of the CT Scan examination, public knowledge in the sufficient category is 42 (42%). Based on the age of the community with an age range of 20-24 years, 30 (30%). Based on gender, people with female gender have sufficient knowledge, namely 27 (27%). Based on the level of education, people with high school education have sufficient knowledge, namely 28 (28%). The conclusion from the results of this study is that the level of public knowledge about CT Scan examination in Condongcatur village is in the sufficient category, namely 42 (42%).